A Dynamic Interactive Approach to Music Listening: The Role of Entrainment, Attunement and Resonance - Mark Reybrouck (Multimodal Technologies and Interaction, 2023)
This paper takes a dynamic interactive stance to music listening. It revolves around the focal concept of entrainment as an operational tool for the description of fine-grained dynamics between the music as an entraining stimulus and the listener as an entrained subject. Listeners, in this view, can be “entrained” by the sounds at several levels of processing, dependent on the degree of attunement and alignment of their attention. The concept of entrainment, however, is somewhat ill-defined, with distinct conceptual labels, such as external vs. mutual, symmetrical vs. asymmetrical, metrical vs. non-metrical, within-persons and between-person, and physical vs. cognitive entrainment. The boundaries between entrainment, resonance, and synchronization are also not always very clear. There is, as such, a need for a broadened approach to entrainment, taking as a starting point the concept of oscillators that interact with each other in a continuous and ongoing way, and relying on the theoretical framework of interaction dynamics and the concept of adaptation. Entrainment, in this broadened view, is seen as an adaptive process that accommodates to the music under the influence of both the attentional direction of the listener and the configurations of the sounding stimuli.